Arsenic removal procedure for the electrolyte from a hydro-pyrometallurgical complex. (October 2021) - Paz-Gómez, D.C.; Pérez-Moreno, S.M.; Gázquez, M.J.; Guerrero, J.L.; Ruiz-Oria, I.; Ríos, G.; Bolívar, J.P.
Abstract: Commercial copper (Cu) is obtained by a hydro-pyrometallurgical process, where the Cu anodes obtained in the furnaces (Cu > 99.5%) are enriched up to 99.99% in "cathodes" by electrorefining at an electrolysis plant. During this process, some impurities accumulate in the electrolyte, mainly arsenic (As), which decrease the quality of the Cu cathode. For this reason, the electrolyte is sent to an electrolyte cleaning plant (ECP) for its purification. Electrolyte sludge (ES) is produced in the last stage of purification and is recirculated back to the furnace due to the high Cu content. This recirculation involves a severe problem of As accumulation in the industrial process. The objective of this work was to develop a procedure to fully dissolve the ES, removing the As and recovering its Cu content. The ES dissolution process was optimised (dissolution efficiency > 99%) in H2 SO4 (1.4 M)/HNO3 (1.8 M) medium using a 1:20 g mL −1 solid-to-liquid ratio. As was removed from the ES solution by its precipitation as iron (III) arsenate, with high efficiency (more than 70%). After As removal, the Cu can be precipitated as copper sulphate, which is used in several applications. Graphical abstract: Image 1 Highlights: New procedure for arsenic removal in the electrolyte wastewater from cathode copper. Fully dissolve electrolyte sludge was achieved. High arsenic removal efficiency was obtained.